Partisipasi Masyarakat Terkait Konservasi Hutan Mangrove sebagai Penyeimbang Ekosistem di Desa Apar Kota Pariaman - Nadia Syafitri; Nefilinda Nefilinda; Rozana Eka Putri (Departement of Mathematics Education, 2023)
This research is based on the problems in Apar Village which are the background to the destruction of Mangrove Forests caused by two factors, namely natural factors and human factors. The aim of this research is to analyze and describe 1). Efforts to protect mangrove forests in Apar Village 2). Efforts to preserve mangrove forests in Apar Village 3) Mangrove forests as a balancer for the ecosystem in Apar Village. The type of research used is